GENERASI MUDA MENUJU LOYALITAS HIJAU: NILAI HIJAU YANG DIRASAKAN, KEPUASAN HIJAU, DAN KEPERCAYAAN HIJAU - Conny Tjandra Rahardja; Faradilla Yulvia Pratiwi (Jurnal Ekonomi Dan Bisnis, 2022)
This research involved 248 consumers of green products. The study aims to analyze whether the perceived green value has indirect effect on green loyalty through two mediators: green satisfaction and green trust. This study uses structural equation modeling (SEM) to prove the hypotheses processed with SmartPLS3 software. The findings from this study are green satisfaction and green trust partially mediate the positive effect of green perceived value on green loyalty. Another finding is that each variable of green perceived value, green satisfaction, and green trust has a positive effect on green loyalty. Enhancing in green perceived value will also increase consumer satisfaction and trust.